XXVII Open Seminar on Acoustics, Puławy, 15-19 October, 1980 - ETIENNE, Jerzy; STRASZEWICZ, Witold (Archives of Acoustics, 1981)
The XXVII Seminar on Acoustics (OSA 80) was hold in Puławy on 15-19 October, 1980. It was organized by the Warsaw Division of the Polish Acoustical Society and the Institute of the Fundamental Technological Research of the Polish Academy of Sciences, and the Experimental Department Techpan. The chairman of the Scientific Committee was Prof. Ignacy MALECKI, and the chairman of the Organizing Committee was Dr. Jerzy ETIENNE.